Produção de biodiesel de óleo de algodão utilizando catalisador heterogêneo sintetizado a partir da casca de ovo - Castro, Luciene da Silva (2017)
The search for alternative sources to fossil fuels due to dwindling oil reserves, increasing energy demand and reducing the environmental impact, emerged biodiesel, a biofuel with low toxicity and biodegradable. The synthesis of biodiesel is usually carried out using the transesterification method, which can use both homogeneous catalysts and heterogeneous catalysts to accelerate the reaction. Although the homogeneous catalysis is more used by the industries, it is necessary to perform several washes of the product and there is no recovery of the catalysts. Thus, the use of heterogeneous catalysts can overcome these difficulties, but it has a higher cost. In this paper sought to synthesize the CaO catalyst derived eggshell prepared at different temperatures of calcination for the production of cotton oil biodiesel. The catalysts were prepared from calcination and characterized by the Hammett method, X - ray diffraction (XRD), Thermogravimetry (TG) and Scanning Electron Microscopy (SEM). The catalytic activity was evaluated by the methyl transesterification reaction in triplicate for 3 h, using a 9: 1 molar ratio of methanol: oil, 3% catalyst (mass of catalyst/ oil) at 60 °C. The eggshell is rich in CaCO3, when subjected to heat treatment results in CaO, confirmed by the X - ray Diffraction. The high basicity of the catalysts was demonstrated by the Hammett method. The catalysts had a base strength of 9,8 = H_ < 12,2 and while the in nature shell eggshell had H_= 3.5. The calcination temperature exerted a strong influence on the heat treatment. The eggshell morphology was thermally modified. The catalysts exhibited good thermal stability. The transesterification reaction of the catalysts calcined at 800 °C, at 900 °C and at 1000 °C achieved an ester conversion of 97.83% and 97.23% and 98.08% respectively. Catalysts are promising for the production of biodiesel.